CHALLENGES IN MEDICO-LEGAL AUTOPSY DURING COVID-19 PANDEMIC TIMES - Kumaran, Senthil; Janarthanan, Venkatesh; Raj K, Karthi Vignesh (Journal of Forensic Medicine and Toxicology, 2021)
The COVID-19 pandemic caused by 2019-nCoV outbreaks in most of the countries has spread rapidly and became a major concern. Due to the strong infectivity nature of COVID-19 and lack of experience among forensic experts in performing autopsy during this period, it has been a challenge and a learning experience for the future. In this article, we summarize what are the issues faced and managed during and after medico-legal autopsy of confirmed or suspected cases.
Keywords: COVID-19; coronavirus; dead body management; autopsy protocol